PENINGKATAN KREATIVITAS PESERTA DIDIK MELALUI KEGIATAN MEMBUAT KARYA SENI KOLASE DI SEKOLAH DASAR - Waryd Sydik; Arsyi Rizqia Amalia; Dyah Lyesmaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the lack of creativity in students. Students' creativity still tends to be lacking due to learning that does not provide stimulation for students' creativity. One of the activities that can develop students' creativity is the activity of making collages. Collage making activities allow students to explore and express their imagination to be more creative. This research aims to increase students' creativity with collage making activities. The research method used in this study is classroom action research with the Kemmis and Taggart model which is carried out through four stages, namely planning, action, observation and reflection. The subject of this study is 24 students in grade IV of SDN Ranji. Data collection techniques are carried out by performance, observation and documentation. The results of the study showed that there was an increase in students' creativity with the activity of making collages as evidenced through performance assessments. The results of the study showed that there was an increase in complete students during the pre-cycle of students or 54.17% of the number of students. Cycles I and II also increased, originally 54.17% increased to 83.33% of the number of students in the class. The percentage of completeness shows that the activity of making collages can increase students' creativity.